A case study of green building in Malaysia: cost saving analysis - Soon, C. K.; Zaini, Z.; Mohd Ujang, A.; Nagapan, S.; Abdullah, A. H.; Hasmori, M. F.; Rassiah, K. (Universiti Putra Malaysia Press, 2017)
The building sector consumes about forty percent of world energy, making energy efficiency in existing buildings an important issue. This study has been undertaken to investigate energy consumption of a building that has been redesigned to incorporate energy efficient features. It was found that the introduction of energy efficient features has helped to achieve savings up to 46% of the total spent on energy particularly based on electricity bills.